Single step green synthesis of nickel and nickel oxide nanoparticles from Hordeum vulgare for photocatalytic degradation of methylene blue dye. Issue 4 (2nd April 2020) - Din, Muhammad Imran; Tariq, Maria; Hussain, Zaib; Khalid, Rida
Abstract: A novel and facile green approach was adopted for carrying out the large scale synthesis of the nickel (Ni) and nickel oxide (NiO) nanoparticles (NPs). The seeds extract of Hordeum vulgare plant which is rich in phenolic content and antioxidants was utilized for reducing the precursor metal salt into NPs. The results of UV/Vis spectroscopy revealed that the synthesized nanoparticles were monodispersed in nature and plant extract controlled the particle size effectively. FTIR spectrum revealed that amines and phenolic groups of the plant were responsible for the formation and stabilization of Ni nanoparticles. The best yield of nanoparticles was obtained at pH 12 using 1 M salt solution, temperature of 60 °C and heating time of 60 minutes. The catalytic activity of synthesized nanoparticles was checked by degradation of methylene blue dye and it was found that degradation of the dye followed first order kinetics.